Strongly coupled stimulated Brillouin amplification in pump-ionizing plasma. (16th January 2018) - Peng, H; Wu, Z H; Zuo, Y L; Zhou, K N; Wang, X D; Li, Q; Zhu, H Y; Su, J Q
Abstract: Laser amplification based on strongly coupled stimulated Brillouin scattering in plasma is investigated. The pump and seed are at the same wavelength of 800 nm and the same duration of 3.5 ps, but with a different intensity. The plasma is produced by the front part of the pump via tunnel ionization from hydrogen. The hydrogen is fully ionized to eliminate small-scale density fluctuations in the plasma, so the transmission level of the seed is enhanced to 22%, and a relative amplification factor of 6 is obtained.